Cyanophenylcarbazole isomers exhibiting different UV and visible light excitable room temperature phosphorescence. Issue 31 (25th July 2019) - Wang, Yanhui; Zhang, Zhenzhen; Liu, Linxi; Yuan, Shou; Ma, Jie; Liu, Danfeng; Xue, Shanfeng; Sun, Qikun; Yang, Wenjun
Abstract : Five cyanophenylcarbazole isomers have RTP activity under 365 nm UV and 400–460 nm visible light excitation but exhibit different RTP intensities and lifetimes. Abstract : Pure organic luminophores with room temperature phosphorescence (RTP) have been attracting much attention due to their potential applications and academic importance. The development of such materials with visible light-excitability and the understanding of the structure–property relationship are highly desirable. In the current work, the five structural isomers of cyano-substituted phenylcarbazoles with cyano at the para -, meta -, and ortho -position of the phenyl ring (PCN, MCN and OCN) and the 2- and 3-position of the carbazole ring (2CN, 3CN) are systematically designed and synthesized. These crystals all have RTP activity under 365 nm UV and 400–460 nm visible light excitation but exhibit different RTP intensities and lifetimes. The crystal packing analysis and quantum chemical calculations as well as low temperature phosphorescence measurements indicate that cyano substitution can greatly enhance intermolecular CH⋯N and CH⋯π interactions and increase inter-system crossing probability, but the structural isomerism can significantly affect the oxygen quenching effect on RTP. Moreover, 2CN and 3CN crystals with H-aggregation are more favorable for the visible-light excitable RTP. These findings indicate that structural isomerism can tune the crystal packing modes and the visible-light excitable RTP as well as the existence of the direct triplet state population from the ground state.